Nickel‐Catalyzed Carboxylation of Benzylic C−N Bonds with CO2. (15th March 2016) - Moragas, Toni; Gaydou, Morgane; Martin, Ruben
Abstract: A user‐friendly Ni‐catalyzed reductive carboxylation of benzylic C−N bonds with CO2 is described. This procedure outperforms state‐of‐the‐art techniques for the carboxylation of benzyl electrophiles by avoiding commonly observed parasitic pathways, such as homodimerization or β‐hydride elimination, thus leading to new knowledge in cross‐electrophile reactions.